Modern Aspects of Endoprosthetics in Hip Joint Osteoarthritis - Kamariddin Kh. Khisomov; Vyacheslav S. Ondar (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
The surgical procedure for an artificial joint - the endoprosthesis implantation significantly improves the patient's quality of life andhas a significant impact on his rehabilitation optimizing, necessary for a normal life in the future. Due to its anatomical characteristicsand biomechanical ratio, the hip joint plays a critical role in maintaining body balance and proper gait. Endoprosthesis is used ina significant hip joint function disorder. Indications for the endoprosthesis may be degenerative changes, various injuries or somecongenital disorders. A degenerative change, like coxarthrosis, leads to surgery due to its progression in almost all cases. Depending onan operator and a patient, this procedure can be performed in several ways depending on the chosen access to a thigh. Today, the directaccess is most commonly used from the front, side, and rear. The difference is in a place of entry into the joint and the damage to themuscles caused by the procedure itself. Physiotherapy is required after the procedure. The process of physiotherapy begins immediatelyafter the surgery, on the first day after the procedure. It is believed that, in the period of three to four months after rehabilitation, thepatient can return to almost all the previous usual activities, of course, after examination and consultation with the doctor.Aim. To analyze the literature data on modern aspects of arthroplasty in the hip joint osteoarthrosisResults. Various arthroplasty complications in coxarthrosis can be associated with errors in the surgery techniques, as well as the lackof patients' motivation. The number of studies concerning quality of life and therefore health is growing, and the research results canbe used as relevant ones to represent the state of each individual group.